The musical intelligence as a basic competition in parvular teacher - Alcivar, Carmen Magdalena Mero (International Journal of Psychosocial Rehabilitation, 2020)
In the Jama Educational Unit, there are preschool classrooms, where it has been noticed that the musical strategies are not applied correctly in the teaching process, the research has been aimed at knowing the level of competence in the learning of musical intelligence in kindergarten teachers, to complete it an instrument was applied through the use of the survey of teachers that are directly linked to this level of education today, noting that all respondents meet the basic aspects evaluated in relation to the use of musical techniques, to enhance multiple intelligence at the nursery level; It was obtained as a result that the pedagogues of the investigated unit, however, it was observed that they do not satisfactorily apply musical intelligence, as a tool or work strategy in the classroom to improve the integration process of the students.